Evolving Determinants of Childhood Stunting: A Comparative Analysis in 514 Districts in Indonesia Before and After COVID-19 Pandemics - Eflita Meiyetriani; Budi Utomo (Nusantara Science and Technology Proceedings, 2024)
Stunting is a health issue that requires serious attention due to its impact on the growth and development of children. This study investigates the determinants of stunting among children in 514 districts in Indonesia, with a focus on the impact of various socio-economic and environmental factors using secondary data from Badan Pangan Nasional in 2018-2019 and 2022-2023 which was published online. Two separate models were employed for periods before and after the COVID-19 pandemic using multivariate linear regression. For the period before the COVID-19 pandemic (2018-2019), the model reveals significant associations between stunting and several variables including life expectancy, food expenditure, nutritional consumption per capita, and healthcare workforce ratio. However, the impact of some factors such as the duration of female schooling, and lack of clean water, and electricity was not statistically significant. In contrast, the model for the period after the COVID-19 pandemic (2022-2023) shows a different pattern of associations. Here, stunting is significantly correlated with life expectancy, duration of female schooling, nutritional consumption per capita, healthcare workforce ratio, and access to clean water, while factors such as poverty, food expenditure, and access to electricity show weaker or statistically insignificant associations. These findings highlight the evolving nature of factors contributing to childhood stunting, suggesting the need for tailored interventions addressing socio-economic and environmental determinants to combat this pressing public health issue effectively.